2003
DOI: 10.1177/0095399702250467
|View full text |Cite
|
Sign up to set email alerts
|

The role of controlled and dynamic process environments in group decision making: An exploratory study

Abstract: Information systems have focussed on controlling the decision-making environment, whereas in real life groups operate in an uncontrolled, asynchronous environment. In this article, we examine existing information system research on groups, analyze the role played by the process environment on the quality of group decisions, and argue the need for the design and research into information systems for uncontrolled dynamic environments. The recent growth of the Internet and Internet-mediated simulations provide un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 44 publications
0
3
0
1
Order By: Relevance
“…In 2003, a special issue of Communications of the ACM, named "A Game Experience in Every Application," was dedicated to simulation games in diverse applications. Over the years, researchers have reported on the extent of usage of simulation games in academe and business (e.g., [1], [5], [15], [16]). However, simulations created especially for research purposes are usually oversimplified and less realistic.…”
Section: Business Simulation Gamesmentioning
confidence: 99%
“…In 2003, a special issue of Communications of the ACM, named "A Game Experience in Every Application," was dedicated to simulation games in diverse applications. Over the years, researchers have reported on the extent of usage of simulation games in academe and business (e.g., [1], [5], [15], [16]). However, simulations created especially for research purposes are usually oversimplified and less realistic.…”
Section: Business Simulation Gamesmentioning
confidence: 99%
“…Research on group decision support systems (GDSS) has revealed that these systems result in more time to make a decision, higher decision quality, better overall performance, and a higher degree of satisfaction with the decision (Dasgupta, 2003). Dasgupta points out that most GDSS studies have taken place in highly controlled environments.…”
Section: Research Study X Decision-making Leadership and Interpersmentioning
confidence: 99%
“…His paper briefs the research carried out by many others on the usage of simulation games in academics and business and chooses Asakawa and Gilbert (2003), Dasgupta ( 2003), Eldredge and Watson (1996), Faria (1987Faria ( , 1998; Haapasalo and Hyvonen (2001), Larréché (1987), Lucas and Nielson (1980) and Muhs and Justis (1981) as some of the examples.…”
Section: Introductionmentioning
confidence: 99%